Identification of odontogenic ameloblast associated as a novel target gene of the Wnt/β‐catenin signaling pathway. Issue 3 (29th November 2022) - Yamaguchi, Kiyoshi; Horie, Chiaki; Takane, Kiyoko; Ikenoue, Tsuneo; Nakagawa, Saya; Isobe, Yumiko; Ota, Yasunori; Ushiku, Tetsuo; Tanaka, Mariko; Fujishiro, Jun; Hoshino, Noriko; Arisue, Atsuhiro; et al.
Abstract: The Wnt/β‐catenin signaling pathway plays a key role in development and carcinogenesis. Although some target genes of this signaling have been identified in various tissues and neoplasms, the comprehensive understanding of the target genes and their roles in the development of human cancer, including hepatoma and colorectal cancer remain to be fully elucidated. In this study, we searched for genes regulated by the Wnt signaling in liver cancer using HuH‐7 hepatoma cells. A comparison of the expression profiles between cells expressing an active form of mutant β‐catenin and cells expressing enhanced green fluorescent protein (EGFP) identified seven genes upregulated by the mutant β‐catenin gene ( CTNNB1 ). Among the seven genes, we focused in this study on ODAM, odontogenic,  ameloblast associated, as a novel target gene. Interestingly, its expression was frequently upregulated in hepatocellular carcinoma, colorectal adenocarcinoma, and hepatoblastoma. We additionally identified a distant enhancer region that was associated with the β‐catenin/TCF7L2 complex. Further analyses revealed that ODAM plays an important role in the regulation of the cell cycle, DNA synthesis, and cell proliferation. These data may be useful for clarification of the main molecular mechanism(s) underlying these cancers. Abstract : We have identified odontogenic ameloblast associated (ODAM) as a novel target gene of the Wnt/ß‐catenin signaling. Its expression is augmented in the majority of hepatoblastoma cells, and some hepatocellular and colorectal carcinoma cells. Elevated ODAM expression is associated with the proliferation of tumor cells.